Aerodynamics analysis of wheel configurations in Paralympic hand-cycling: A computational study - Mannion, P.; Toparlar, Y.; Hajdukiewicz, M.; Clifford, E.; Andrianne, T.; Blocken, B. (European Journal of Mechanics - B/Fluids, 2018)
Para-cycling aerodynamics holds additional complexities compared to its able-bodied counterpart. Hand-cycling provides such an example, where three wheels opposed to the two wheels of a traditional bicycle are required. Wheel aerodynamics are therefore even more prevalent in the field of Paralympic hand-cycling. However, there has been little attention devoted to wheel aerodynamics in Paralympic hand-cycling. This study investigates hand-cycling wheel aerodynamics. The optimal wheel selection was investigated from a combination of wheels that represented competitive deep-section spoked wheels and disk wheels. In addition to the various wheel combinations, the spacing between the two rear wheels was varied. A 55 cm rear wheel spacing provided drag reductions of up to 4.7% compared to 70 cm when using rear disk wheels at 0°yaw. Crosswinds were also investigated, and it was shown that a front disk wheel coupled with rear deep-section wheels at 55 cm spacing provided the best aerodynamic drag performance with increasing yaw angle. With this wheel setup, the CDA increased by only 7.7%, between min and max values found at 0°and 15°yaw respectively.